Disorders of eating behavior at different phenotypes of obesity in children - A.E. Abaturov; A.A. Nikulina (Zaslavsky O.Yu., 2020)
Background. Eating disorders, formed in childhood, cause a high level of obesity, including its complicated course, throughout the world and require personalized preventive interventions. The purpose was to study the associations of the type of eating behavior with the phenotypes of obesity in children aged 6-16 years old. Materials and methods. One-hundred and nine 109 children with polygenic obesity aged 6-16 years were examined. The first group (n = 40) included patients with the phenotype of metabolically unhealthy obesity, the second group (n = 69) was formed by patients with the phenotype of metabolically healthy obesity. The recommendations of the expert group of the National Heart, Lung, and Blood Institute (NHLBI) were used as criteria for metabolically unhealthy obesity in children and adolescents. The Dutch DEBQ questionnaire was used to assess the type of eating behavior. The emotional type of eating behavior was determined when evaluated on the corresponding DEBQ scale more than 1.8 points, the external type - when assessed on the corresponding DEBQ scale more than 2.7 points and the restrictive type - when assessed on the corresponding DEBQ scale more than 2.4 points. Results. External (3.48 ± 0.16 points; 52.50 ± 5.09 %) and emotiogenic (2.92 ± 0.24 points; 34.20 ± 5.92 %) types of eating disorders were equally often diagnosed in children suffering from metabolically unhealthy obesity with a moderate degree of deviation above normal, p > 0.05. The restrictive type of eating behavior was observed in the phenotype of metabolically healthy obesity (2.52 ± 0.20 points, with a very low degree of deviation above the norm of 9.40 ± 2.92 %). Conclusions. Eating behaviors in children aged 6-16 years are associated with obesity phenotypes and require personalized nutritional modification. The external type of eating behavior has the greatest correlation with the formation of the phenotype of metabolically unhealthy obesity, while the phenotype of metabolically healthy obesity correlates with the restrictive type of eating behavior.